If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-4x + 4) = 0 Reorder the terms: 2(4 + -4x) = 0 (4 * 2 + -4x * 2) = 0 (8 + -8x) = 0 Solving 8 + -8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -8x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -8x = 0 + -8 -8x = 0 + -8 Combine like terms: 0 + -8 = -8 -8x = -8 Divide each side by '-8'. x = 1 Simplifying x = 1
| 56x^4+24x^3+56x^2/8x^3 | | 16/7=10.5/b | | 2x/3+5/6=3x/2 | | 2x^2+6x-3=o | | (n/9)-(7n/18)=1/9 | | -7x+3x-2x=0 | | 1/3+3/3m=2/3m-2/3 | | 124/4*x=24 | | -12-7n=-2 | | -4(-m+2)+2m=-0.5(10-12m)-3 | | 10b+3b= | | V=3.14r*3.14rh | | 72x^2+96x=0 | | 6v^2+23v+21/4v^2-4v-15*4v^2-25/3v+7=0 | | 7(n-8)=8n-7 | | 3x+2+(x-5)=6x-23 | | 8x-5(-2x+2)=44 | | 9+5x+2x=-68 | | 6m+13=9m-2 | | 4/5-2=10 | | 180/60b=1200 | | r-1.1=0.3 | | 18=29+a | | x/2=x+5/3 | | .7x+.3y=35 | | (3)(-3)= | | 21*10/3/x=113 | | 9v-45=6(v-6) | | (5)(5)= | | 6c-15=2c+45 | | -2(6-3x)=18 | | 35*3+x=23 |